Chronic diarrhoea in protein-energy malnutrition - Michael Gracey (Indonesian Pediatric Society, 1981)
Infection and malnutrition exemplify synergistic role of these two major factors in the pathogenesis of diarrhoea in protein-energy malnutrition.